Mathematical Modelling of Truck Platoon Formation Based on a Dynamic String Stability - Ore Ofe Ajayi; Abubakar Umar; Ibrahim Ibrahim; Lawal Abdulwahab Olugbenga; Ajikanle Abdulbasit Abiola (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
In this research, developinga Fuzzy Logic Cooperative Adaptive Cruise Control (FCACC) scheme significantly enhanced truck platooning string stability by ensuring rapid stabilization and robustness against disturbances. The mathematical model designed and implemented in SUMO/OMNeT++ simulated various scenarios, demonstrating the superiority of the FCACC over conventional CACC, PATH CACC, and Ploeg CACC controllers. Quantitatively, the FCACC achieved velocity and spacing stability within an average of 7.33 seconds and 4.39 seconds using the triangular-centroid method, outperforming the CACC, PATH CACC, and Ploeg CACC by 28.09%, 25.21%, and 22.26% for velocity stability and 31.69%, 29.96%, and 28.01% for spacing stability, respectively. Additionally, the FCACC reduced the Expected Arrival Time (EAT) deviation by 4.62% compared to the CACC, demonstrating its efficiency in handling disturbances such as truck breakdowns. The FCACC's rapid stabilization, even in the presence of impulse signal disturbances, was evident in its ability to recover within 2.3 seconds for speed and 3.6 seconds for distance, compared to 27.5 seconds and 10.1 seconds for CACC. The fuzzy-PLEXE framework further emphasized the FCACC’s advantage by inducing more minordistance errors and faster stability times than other models, achieving stability in 53 seconds versus 60 seconds for Ploeg CACC. These results underline the FCACC’s efficacy in mitigating unexpected disruptions and maintaining optimal string stability. However, limitations such as dependency on precise sensor data, susceptibility to communication delays, and challenges with scalability for larger platoons were observed, suggesting areas for future optimization.